2011
DOI: 10.1101/gad.2038811
|View full text |Cite
|
Sign up to set email alerts
|

Limiting Ago protein restricts RNAi and microRNA biogenesis during early development in Xenopus laevis

Abstract: We show that, in Xenopus laevis oocytes and early embryos, double-stranded exogenous siRNAs cannot function as microRNA (miRNA) mimics in either deadenylation or guided mRNA cleavage (RNAi). Instead, siRNAs saturate and inactivate maternal Argonaute (Ago) proteins, which are present in low amounts but are needed for Dicer processing of pre-miRNAs at the midblastula transition (MBT). Consequently, siRNAs impair accumulation of newly made miRNAs, such as the abundant embryonic pre-miR-427, but inhibition dissipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 70 publications
4
88
0
Order By: Relevance
“…Alternatively, if artificially synthesized piRNA precursors (Kawaoka et al 2011) or piRNA mimics of 23-30 nt in length are effectively introduced by transfection or microinjection into cells with an active piRNA pathway, they could also cause specific silencing. The piRNA-mediated gene knockdown might also be useful in early embryos or oocytes of some animals such as Xenopus since RNAi and miRNA biogenesis are restricted in these species due to the limited amount of the Argonaute proteins (Lund et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, if artificially synthesized piRNA precursors (Kawaoka et al 2011) or piRNA mimics of 23-30 nt in length are effectively introduced by transfection or microinjection into cells with an active piRNA pathway, they could also cause specific silencing. The piRNA-mediated gene knockdown might also be useful in early embryos or oocytes of some animals such as Xenopus since RNAi and miRNA biogenesis are restricted in these species due to the limited amount of the Argonaute proteins (Lund et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…The enzyme dicer that cleaves pre-miRNA into mature miRNA, have only one fourth of the activity in X. laevis oocytes compared to matured cells (Lund et al, 2011;Muggenhumer, 2010;Muggenhumer et al, 2014). Therefore, the Na channel activity is only suppressed by 58 % in oocytes expressing miRNA-SCN2A ( figure 1c in paper III).…”
Section: Resultsmentioning
confidence: 98%
“…However, in X. laevis oocytes, cDNA plasmids expressing premiRNA need to be injected into the nucleus for it to be transcribed ( Fig. 3) (Lund et al, 2011). In the nucleus, pre-miRNA is bound to exportin 5 (EXP5) and cofactor Ran that has GTP bound to it.…”
Section: Mirna Expressionmentioning
confidence: 99%
“…A recent study suggests that this is due to a lack of the Argonaute-2 (Ago2) protein in embryos. Ago2 is necessary for dicer dependent nuclease activity and Lund et al have shown that expression of exogenous Ago2 is sufficient for RNAi activity in Xenopus (Lund et al, 2011). However, for many years RNAi seemed impossible in Xenopus; therefore, studies in Xenopus have made use of synthetic nonnatural oligonucleotides to target RNA activity, summarized in Table 4.…”
Section: Controlling Translation With Small Moleculesmentioning
confidence: 99%